Analyzing the effect of government subsidy on the development of the remanufacturing industry - Zhou, Qin (2021)
Remanufacturing plays an important role in a circular economy, by shifting supply chains from linear to closed loop. However, the development of the remanufacturing industry faces many challenges. Consumers’ uncertainty about the quality of remanufactured products can hamper their decision to make a purchase (i.e., uncertainty behavior). Such uncertainty can be reduced when they learn that more consumers are purchasing remanufactured products (i.e., network externality behavior). Considering the aforementioned behaviors, this paper investigates how a government could set the optimal subsidy level to maximize the sales quantity of remanufactured products with a limited budget. We modeled a Stackelberg game between the government and an original equipment manufacturer, under two settings, over two periods. Setting 1 only considers an original equipment manufacturer that produces remanufactured products, and Setting 2 considers an original equipment manufacturer that produces both new and remanufactured products. We show that the original equipment manufacturer should adjust its pricing strategy (i.e., markup vs. markdown) according to the subsidy levels. Our analysis on the government budget constraint shows that an original equipment manufacturer earns more profits in Setting 1 than Setting 2, only when the budget constraint is high, and less profits when budget constraint is low.